Preliminary Novel Analysis on Antimicrobial Properties of Concentrated Growth Factor Against Bacteria-induced Oral Diseases - Muhammad Syafiq Alauddin; Nabilah Mohd Yusof; Aini Sufinah Adnan; Zulfahmi Said (Thieme Medical and Scientific Publishers Pvt. Ltd., 2024)
Indexed by Scopus